Faculty Senate, Minutes, February 15, 2001 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2001)
Valdosta State University. Faculty Senate, Minutes, February 15, 2001. Chairman, President H. C. Bailey; Vice Chairman, Vice President L. Levy; Executive Secretary, Dr. R. Hull; Parliamentarian, Dr J. Wheeler;
1 electronic document. Faculty Senate, Minutes, February 15, 2001. 5 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records